Casing running and solidifying bore by grouting in directional long borehole in coal mine - Yanjun FENG; Hong HOU; Jianchao REN; Maofu LIU; Liqiang SUN (Meikuang Anquan)
To solve the current problem that it is difficult to realize the whole process of running the thick diameter casing and solidifying bore by grouting in the hydraulic fracturing of directional long boreholes in underground coal mines, we analyzed the technical difficulties of casing running and solidifying bore by grouting and the corresponding countermeasures were presented. The overall technical scheme of casing running and solidifying bore by grouting in directional long borehole was constructed, the salvable method of casing running and grouting technology through annular space were proposed; the maximum curvature 0.285°/m of the borehole was given by the analysis of casing possibility; the salvable reaming drilling tools, torsion transmission mechanism, spiral centralizer and casing thread type were designed; the grouting technique and cement slurry system which was applicable to upward directional long borehole were developed. The salvable method of casing running and grouting technology through annular space in directional long borehole has been applied to Caojiatan Mine, and application results showed that the technical system is feasible, and the casing with a diameter of ϕ127 mm was drilled to a depth of more than 500 m in a directional long borehole in a coal mine for the first time, and full hole section grouting is realized in directional long holes with hole depth of more than 500 m.